PENGARUH UNSUR RESIKO TERHADAP HARGA OBLIGASI - Syafri, Syafri (Sekolah Tinggi Ilmu Ekonomi H. Agus Salim Bukittinggi, 2008)
The analysis of the bond price uses the cross sectional data of 2000 of corporate bonds listed in the Surabaya Stock Exchange. Based on the WLS method, theresult shows that the price of bonds is influenced by the risk of the bonds, which represented by the rating grade, type and common risk of the bonds variables. The rating grade and type of bonds have a positif influence on the price of bonds while the common risk of bonds has a negatif impact on price of bonds.